PENGEMBANGAN MATERI EVALUASI PEMBELAJARAN BERBASIS WORDWALL UNTUK SISWA SEKOLAH DASAR - Hasanah, Nurhandayani; Sutiah, Sutiah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
Monotonous and repetitive types of evaluation can make children less interested and involved when answering evaluation questions. When evaluations are conducted routinely in the same pattern, such as using only written or multiple-choice tests, students may feel bored and lose interest in the evaluation process. To address this issue, it is important for teachers to vary the type of evaluation used. Using technology-based types of evaluation such as wordwall can make the evaluation process more interesting and enjoyable for students. This study aimed to test the validity and practicality of using Wordwall educational game media in auditory organ system material in grade IV elementary school. This study uses the ASSURE model development type method (Analyzing, Selecting, Organizing, Utilizing, Reflecting, Evaluating). Based on the results of the research data, it can be concluded that using the word wall evaluation tool in grade IV elementary school learning as follows: The quality of validity with word wall resulted in a percentage of validity of 79.8% with practical categories, while in validity using media by material experts obtained a percentage score of 86% with feasible or valid criteria. Meanwhile, from the validity of media experts, the percentage is 80% valid.